Review and Criticism of the Book Kissaaneiae (History and Literature) - Ali-Akbar Abbasi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article aimed to investigate Vedad-al-Ghazi's views, the author of the book entitled as "Kissaniah Sect". This study was based on descriptive-analytic approach and was documented upon the references. Since Vedad-al-Ghazi was proficient in Arabs literature, he could successfully exploit traditional Arabic references and hand-written documents about Kissaniah Sect. He has used Kissaniah's poems and the opposite views to analyze dark points of Kissaniah's history and has gained important creativities in this regard. To investigate the ambiguous points related to Kissaniah, he has proposed some speculations which are not in accordance with history.  He has mentioned that Abdellahibn Saba was a real person, contrary to the doubts about his historical existence. He has also argued many Sabiah's activities. He has not investigated Ali's (PBUH) statements about his son, Mohammad. Furthermore, he has assigned many activities done by Ghaliah to Mokhtar himself. Vedad-al-Ghazi has ignored to investigate holy Quran verses and Prophet Mohammad's statements to describe the concepts of Rajath and Al-gayba.